Meeting the challenges of implementing rapid genomic testing in acute pediatric care. (December 2018) - Stark, Zornitza; Lunke, Sebastian; Brett, Gemma; Tan, Natalie; Stapleton, Rachel; Kumble, Smitha; Yeung, Alison; Phelan, Dean; Chong, Belinda; Fanjul-Fernandez, Miriam; Marum, Justine; Hunter, Matthew; et al.
Abstract Purpose The purpose of the study was to implement and prospectively evaluate the outcomes of a rapid genomic diagnosis program at two pediatric tertiary centers. Methods Rapid singleton whole-exome sequencing (rWES) was performed in acutely unwell pediatric patients with suspected monogenic disorders. Laboratory and clinical barriers to implementation were addressed through continuous multidisciplinary review of process parameters. Diagnostic and clinical utility and cost-effectiveness of rWES were assessed. Results Of 40 enrolled patients, 21 (52.5%) received a diagnosis, with median time to report of 16 days (range 9–109 days). A result was provided during the first hospital admission in 28 of 36 inpatients (78%). Clinical management changed in 12 of the 21 diagnosed patients (57%), including the provision of lifesaving treatment, avoidance of invasive biopsies, and palliative care guidance. The cost per diagnosis was AU13, 388 (US10, 453). Additional cost savings from avoidance of planned tests and procedures and reduced length of stay are estimated to be around AU543, 178 (US424, 101). The clear relative advantage of rWES, joint clinical and laboratory leadership, and the creation of a multidisciplinary "rapid team" were key to successful implementation. Conclusion Rapid genomic testing in acute pediatrics is not only feasible but also cost-effective, and has high diagnostic and clinical utility. It requires a whole-of-system approach for successful implementation.